Full-length single-molecule sequencing uncovers novel insight into the global landscape of the cold stress response in trifoliate orange (Citrus trifoliata) - Wang, Yue; Fang, Tian; Liu, Jihong (Frontiers in Plant Science, 2024)
Trifoliate orange (Citrus trifoliata (L.) Raf.) is a cold-hardy citrus species that contributes to citrus production by frequently serving as a rootstock. Nevertheless, the molecular mechanisms, particularly the post-transcriptional regulation that underlies cold tolerance in citrus remained largely unidentified. In this study, we constructed a transcriptome map of trifoliate orange subjected to cold stress by integrating full-length single-molecule sequencing and Illumina short-read sequencing. The hybrid sequencing approach yielded a more comprehensive set of full-length transcripts than was previously available from the reference genome. In particular, the high-quality transcripts enabled the detection of extensive alternative splicing (AS), with intron retention (IR) identified as the predominant AS event in trifoliate orange. Transcriptome analysis revealed that genes associated with starch and sucrose metabolism were significantly enriched among the cold-responsive genes. Consistent with these data, soluble sugar content was elevated by the cold treatments. Additionally, the expression of multiple genes encoding enzymes with antioxidant activity, including PODs and SODs, was induced, which plays a pivotal role in the mitigation of continuous ROS production. Furthermore, we observed that AS and transcriptional regulation modulate distinct pathways. We also found that the expression of genes encoding key transcription factors (TFs) was highly induced by cold stress and that some of the mRNAs encoding these key TFs were differentially spliced. This dataset provides comprehensive transcriptional and post-transcriptional profiles of the response to cold stress in trifoliate orange that may help to identify genes that contribute to cold tolerance in citrus.